Vidas armadas de desechos: La comercialización de la excreta canina por los grupos menesterosos durante las matanzas de perros vagabundos de la Ciudad de México, 1779-1821 - Luna Loranca, Arturo (Pontificia Universidad Católica del Perú, 2022)
In the late eighteenth and early nineteenth century, the authorities of Mexico City carried out a series of slaughters of so-called vagabond dogs (strays), which claimed the lives of 20,000 to 30,000 canines. The sacrifice of these animals was not well-received by certain sectors of society. This article argues that studying the material relationships established between dogs and plebian groups can partly help explain the reluctance demonstrated by the residents of Mexico City towards the slaughters. Its central argument is that plebian groups did not share the same view as colonial authorities of dogs. While authorities regarded dogs as a latent danger, plebian groups saw dogs as producers of a monetizable good: excreta. Some economic sectors, such as the medical marketplace and leather tanneries, had a high demand for dog excrement.

A finales del siglo XVIII y principios del XIX, las autoridades de la Ciudad de México llevaron a cabo una serie de matanzas de perros vagabundos o callejeros, las cuales cobraron la vida de entre veinte mil y treinta mil caninos. El sacrificio de estos animales no fue bien recibido por ciertos sectores de la sociedad. El artículo arguye que la reticencia expresada por la población de la Ciudad de México hacia las matanzas se puede explicar, en parte, al estudiar las relaciones materiales entabladas entre los perros y grupos menesterosos. El argumento principal es que estos últimos no compartían los mismos valores que las autoridades virreinales. Mientras que para las autoridades el perro representaba un peligro latente, para los grupos menesterosos este animal era un productor de un bien que les representaba ingresos: la excreta. Este producto tenía alta demanda en sectores económicos como el de la salud y en las curtidurías de pieles.
Lives Made from Detritus: The Commercialization of Canine Excreta by the Plebian Groups During Mexico City’s Massacres of Vagabond Dogs, 1779-1821
Keywords: Dogs; Excreta; Garbage; Working poor; Commodification; Perros; Excreta; Basura; Menesteroso; Comodificación; https://purl.org/pe-repo/ocde/ford#6.01.01